Educator Evaluation Policy that Incorporates EVAAS Value-Added Measures: Undermined Intentions and Exacerbated Inequities - Kimberly Kappler Hewitt (Arizona State University, 2015)
In the United States, policies in forty states and D.C. incorporate student growth measures - estimates of student progress attributed to educators - into educator evaluation. The federal government positions such policies as levers for ensuring that more students are taught by effective teachers and that effective educators are more equitably distributed amongst schools. Because these policies are new, little is known about how educators respond to them. Mixed methods survey data from a large, diverse district in North Carolina, a state that incorporates value-added data into teacher evaluations, indicate that substantive, unintended effects may undermine the purposes for which these policies were developed. Results indicate that educators evaluated by value-added are generally opposed to its use. Those who have previously been evaluated by value-added have significantly more negative perceptions about the fairness and accuracy of value-added, are more opposed to its use in educator evaluation, and are more likely to perceive that it will not result in more equitable distribution of good educators across schools and that educators will avoid working with certain students because of value-added. Respondents perceived effects of the use of value-added for teacher accountability that fall within five themes: 1) Educators increasingly game the system and teach to the test, 2) Teachers increasingly leave the field, 3) Some educators seek to avoid working with certain students and at certain schools, 4) Educators feel an increase in stress, pressure, and anxiety, 5) Educator collaboration is decreasing, and competition is increasing. Based on findings, the author recommends five mid-course policy corrections.